The Effect of the Implementation of Good Corporate Governance (GCG) Principles on Pastor Performance - Maria Sahutala; Denny Tewu (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
The church in its existence cannot be seen as limited to the implementation of the preaching of God's word in every ritual of worship. Therefore, if structuring and governance must be a link in structuring services, then in principle the church must also be viewed from an organisational perspective. On 25 May 1985, GPI Papua was institutionally formed. Its service area is spread over the two administrative regions of Papua and West Papua. As an institution that has 470 Pastors and is spread over 20 chapters, it indicates that the problem of the vastness of the GPI Papua service area, the topographical context and the socio-cultural context have an impact on the service and performance of Pastors as organic employees of GPI Papua who have binding institutional rules. In its findings, the performance of the Pastors is difficult to measure the level of success. By establishing the principles of Good Corporate Governance (GCG), the writing of this article wants to assert that the level of success of the Pastor can be seen from the perspective of the local community. On the other hand, methodologically, the writing of this article uses a qualitative approach by looking at case studies in the congregation.